Evaluation of Immune Responses and Protective Efficacy of a Novel Live Attenuated Salmonella Enteritidis Vaccine Candidate in Chickens - Hyunjin Shin; Tae-Min La; Hong-Jae Lee; Taesoo Kim; Seung-un Song; Eunjin Park; Gyu-Hyung Park; In-Soo Choi; Seung-Yong Park; Joong-Bok Lee; Sang-Won Lee (Vaccines, 2022)
An ideal vaccine for controlling Salmonella infection in chicken flocks should be safe, inducing both humoral and cellular immunity. Live attenuated vaccines against Salmonella Enteritidis (S. Enteritidis) have been used as a potential control method of Salmonella infection in the poultry industry. However, live attenuated vaccines can persistently infect poultry for long periods and can become virulent revertant strains. In this study, we assessed the immune responses and protective efficacy of a temperature-sensitive attenuated S. Enteritidis mutant as a potential vaccine candidate. In addition, we evaluated the combined vaccine administration methods to maximize both humoral and cellular immune responses in chickens induced by the vaccine candidate. Immune responses and protective efficacy were compared between the Oral/IM group, vaccinated using one oral dose at four weeks old and a booster intramuscular dose at seven weeks old, and the IM/Oral group, vaccinated using one intramuscular dose at four weeks old and a booster oral dose at seven weeks old. The Oral/IM group showed stronger immune responses than those of the IM/Oral group. Spleens from the Oral/IM group showed a promising tendency of reduction of challenged Salmonella compared with those of other groups. Overall, the results indicated that the S. Enteritidis mutant strain is a promising live attenuated vaccine candidate with good efficacy.